PENGARUH MACAM PUPUK KANDANG DAN KONSENTRASI PSEUDOMONAS FLUORESCENS PADA HASIL TANAMAN BAWANG MERAH (Allium cepa fa. Ascalonicum,L.) VARITAS CROK KUNING - Hony Kharisma Sejati; Murti Astiningrum; Tujiyanta Tujiyanta (Universitas Tidar, 2017)
Research on the Effect of Various Manure and concentration of Pseudomonas fluorescens on Crop Onion (Allium cepa fa. ascalonicum L.) Varietiy Crok Yellow, was conducted from November 2015 until January 2016 Kaliboto Village, District Bener, Purworejo. The Altitude is 190 m, the soil regosol, the average temperature - daily average 23.15 - 27.2 ° C. Rainfall of 2000 - 3000 mm / year. The method used was factorial (4x3) are arranged in a complete randomized block design with three replications. The first factor is kind of manure without manure, cow manure, chicken manure and manure goat. The second factor is the concentration of Pseudomonas fuorescens 0, 10, 20 ml/l. The analysis showed a wide manure can improve of plant height, leaf number, number of cloves per hill, cloves fresh weight per hill, weight savings per hill of dried cloves and cloves per hill diameter onion. The higher the concentration of Pseudomonas fluorescens to 20 ml/l increased plant height, leaf number, number of cloves per hill, cloves fresh weight per hill and tuber dry weight savings per hill of red onion. Different kinds of manure at different concentrations of Pseudomonas fluorescens give the same results on all parameters observed.